Molecular dynamics simulations of ramp-compressed copper - Higginbotham, A; Hawreliak, J; Bringa, E; Kimminau, G; Park, N; Reed, E; Remington, B; Wark, J (2012)
The compression of solids by a ramped pressure pulse, as opposed to shock compression, affords the potential to create states of solid-state matter at pressures greater than those achievable in diamond anvil cells. A fundamental understanding of this process requires a knowledge of the loading conditions that discriminate between so-called quasi-isentropic (QI) conditions and those pertaining to the higher entropy states produced by shock loading. We present here molecular dynamics simulations of single-crystal copper deformed over a range of strain rates and demonstrate that QI states at high pressure and low temperature can be present even at strain rates in excess of 1012 s -1. These states survive long enough to be studied with novel ultrafast techniques, in principle allowing simple, compact, isentropic compression experiments. Our atomistic simulations, with up to 25 million atoms, simulated for ramp durations of up to 300 ps, show how plastic deformation and melting varies with strain rate. © 2012 American Physical Society.